Arguments regarding the importance of professional empathy of medical students - Viorica OALA (Acta et Commentationes, Sciences of Education, 2023)
The article provides theoretical arguments regarding the scientific significance of professional empathy as an important skill for medical students, which allows them to understand patients at a deeper level, to establish positive and supportive doctor-patient relationships facilitating their recovery in a timely manner. Training medical students in professional empathy reduces stress and anxiety in patients, which can have a positive impact on their overall health and well-being. In addition, showing empathy can help medical students develop long-term relationships and trust with their patients. A careful analysis of the professional standards of doctors and medical courses leads to the final conclusion, that this professional competence is recognized as an important condition for professional activity.